ANALISIS USAHATANI BUNGA KRISAN DI KECAMATAN CIPANAS KABUPATEN CIANJUR - Mahatmayana, I Ketut Manu; Suhaeni, Suhaeni; Fauziah, Syifa; Rafiqah, Imas Wildan (JURNAL AGRIMANSION, 2025)
Chrysanthemum flowers are a horticultural commodity with significant development potential due to their high economic value. One of the chrysanthemum-producing villages is Sindanglaya Village, located in Cipanas Subdistrict, Cianjur Regency. This study aims to analyze the costs, revenues, income, and feasibility of chrysanthemum farming. The research employed a descriptive quantitative approach. The sampling technique used was non-probability sampling, specifically the saturated sampling method. The sample consisted of 25 chrysanthemum farmers in Sindanglaya Village. Data were collected through interviews using a structured questionnaire. The data analysis included cost analysis, revenue analysis, income analysis, R/C ratio, B/C ratio, and break-even point (BEP) analysis for both production and price. The results showed that the total cost of chrysanthemum farming with an average land area of 0.3 hectares was IDR 28,109,563 per planting season. The average revenue was IDR 48,885,000 per season, resulting in an income of IDR 20,775,437 per season. The feasibility analysis indicated that the R/C ratio was 1.739, the B/C ratio was 0.739, the production BEP was 1,874 bunches per planting season, and the price BEP was IDR 8,162.5 per bunch. Based on these findings, it can be concluded that chrysanthemum farming in Sindanglaya Village is profitable and feasible to continue.